Statistical Modeling of Ultrawideband Body-Centric Wireless Channels Considering Room Volume - Miyuki Hirose; Hironobu Yamamoto; Takehiko Kobayashi (International Journal of Antennas and Propagation)
This paper presents the results of a statistical modeling of onbody ultrawideband (UWB) radio channels for wireless body area network (WBAN) applications. Measurements were conducted in five different rooms. A measured delay profile can be divided into two domains; in the first domain (0<t≤4 ns) there is either a direct (for line of sight) or diffracted (for nonline of sight) wave which is dependent on the propagation distance along the perimeter of the body, but essentially unrelated to room volume, and the second domain (t>4 ns) has multipath components that are dominant and dependent on room volume. The first domain was modeled with a conventional power decay law model, and the second domain with a modified Saleh-Valenzuela model considering the room volume. Realizations of the impulse responses are presented based on the composite model and compared with the measured average power delay profiles.